The Effect of Individual Characteristics and Communication on the Performance of Indonesian New Generation Management Commissariat of University of Trunojoyo Madura with Organizational Commitment as an Intervening Variable During the Covid-19 Pandemic - Muflihatul Alia Sofianti; Raden Mas Mochammad Wispandono (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
Human resources are one of the keys to success in any organization and a leader must think about the level of performance of members in the midst of unstable living conditions due to the Covid-19 pandemic. One of the main focuses in improving performance is by paying attention to the characteristics of human resources and reviewing how the communication works between individuals in the organization. The independent variables in this study are individual characteristics and communication, the intervening variable is organizational commitment and the dependent variable is performance. This study uses a quantitative method that the population is the management of Indonesian New Generation Commissariat of University of Trunojoyo Madura with a sampling technique uses simple random sampling which obtained a sample of 43 respondents. The method of collecting data is done by distributing online questionnaires and for data processing uses multiple linear regression analysis and path analysis. The results of this study indicate that individual characteristics and communication partially and simultaneously have a positive and significant effect on organizational commitment and performance, organizational commitment has a positive and significant effect on performance. Individual characteristics and communication also have an indirect effect on performance through the intervening variable of organizational commitment.